2022
DOI: 10.1093/noajnl/vdac005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials targeting neurofibromatoses-associated tumors: a systematic review

Abstract: Background There is a paucity of literature that comprehensively analyzes previous and current clinical trials targeting neurofibromatoses-related tumors. This article aims to provide readers of drug development efforts targeting these tumors by analyzing translational and clinical findings. Methods This systematic review was written according to the PRISMA guidelines. Inclusion criteria were clinical trials involving patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 71 publications
(65 reference statements)
0
11
0
Order By: Relevance
“…A comprehensive understanding of molecular mechanisms in tumor progression of NF2-related tumors will provide opportunities for exploring more efficient treatments. Currently, many drugs are being examined targeting pathways involved in the pathogenesis of NF2 [ 14 , 94 , 143 ]. In this section, clinical trials evaluating the targeted therapies for NF-related tumors are discussed (Fig.…”
Section: Future Therapeutic Perspectivementioning
confidence: 99%
See 3 more Smart Citations
“…A comprehensive understanding of molecular mechanisms in tumor progression of NF2-related tumors will provide opportunities for exploring more efficient treatments. Currently, many drugs are being examined targeting pathways involved in the pathogenesis of NF2 [ 14 , 94 , 143 ]. In this section, clinical trials evaluating the targeted therapies for NF-related tumors are discussed (Fig.…”
Section: Future Therapeutic Perspectivementioning
confidence: 99%
“…Bevacizumab (an anti-VEGF antibody) has demonstrated encouraging results in patients with NF2-associated VS. [ 13 , 14 ] In patients with progressive disease, it has successfully controlled the growth rate and helped to improve the hearing status [ 81 , 154 156 ]. Different studies indicated a 36%–41% partial response of bevacizumab for NF2-related VS in patients 12 years and older [ 14 ]. The therapeutic effect of bevacizumab in pediatrics and adults with smaller and slow-growing tumors was less prominent [ 156 158 ].…”
Section: Future Therapeutic Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…5,6 A recent systematic review highlighted the significant increase in active and planned clinical trials for neurofibromatosis-associated tumors, including plexiform neurofibromas and cutaneous neurofibromas. 7 Plexiform neurofibromas occur in up to 50% of individuals with NF1 and can cause severe morbidity, including pain, disfigurement, motor dysfunction, and airway obstructions. Cutaneous neurofibromas occur in almost all adults with NF1, with the number of individual tumors ranging widely (from a few to multiple thousands) and typically increasing with age.…”
Section: Introductionmentioning
confidence: 99%